Avrupa İnsan Hakları Mahkemesine bireysel başvuru - Yılmaz, Hayati (My University, 2002)
Bu tez çalışmasının amacı Avrupa İnsan hakları Mahkemesine bireysel başvuru usülü ve esaslarının belirlenmesidir. Bireysel başvuru hakkı, üç bölümde incelenmiştir: Birinci bölümde; İnsan hakları kavramı, insan haklarının tarihçesi ve insan haklarının evrenselleş mesi incelenmiş, İkinci bölümde; Avrupa İnsan Hakları Sözleşmesinin hazırlanması ve onaylanması, sözleşmeye çekince konması, sözleşmenin iç hukuktaki yeri, sözleşmenin özellikleri, sözleşme ile korunan haklar ve bu hakların sınırlanması,sözleşme ile öngörülen organlar, Üçüncü bölümde ise Avrupa İnsan Hakları Mahkemesine bireysel başvuru hakkı,mahkemenin yetkisi ve bu yetkiyi tanıma bireysel başvurunun tarafları, başvurunun şekli, başvurunun kabul şartları başvurunun esastan incelenmesi, iç hukuk yollarının kullanılması,başvuru süresi, tüketilmesi gerekli iç hukuk yollarının istisnaları,başvuru için gerekli diğer şartlar ve Avrupa İnsan Hakları Divanı ile komisyonu tarafından verilen kararlar incelenmiştir. The aim of this thesis is to determine the procedure and principles of individual application to Europcan Court of Human Rigts. Right of individual application was studied under three parts: In the first part: The Concept of human rights,history of human rights and the universalisation of human right, In the second part; The preparation and ratification of European Convention on Human Rights, Putting reservation to convention, place of convention in municipal law,properties of convention ,rights protected by convention and restriction of this rights, organs projected by convention, In the third part, Individual application to European Court of Human Rights, jurisdiction of the court and recognition of its jurisdiction, parties of individual application ,from of application, acceptance conditions of application, meritorious review of application to be used methods of Internal Law, Application's duration,Exceptions of methods of Internal Law that is necessary to be used up, other conditions which is necessary for application, and It has been examined decisions which are given by European Court for Human Rights and European Comission for Human Rights.
Keywords: Avrupa İnsan Hakları Mahkemesi